Circulating N-Acetylaspartate does not track brain NAA concentrations, cognitive function or features of small vessel disease in humans - Rebelos Eleni; Daniele Giuseppe; Campi Beatrice; Saba Alessandro; Koskensalo Kalle; Ihalainen Jukka; Saukko Ekaterina; Nuutila Pirjo; Backes Walter H.; Jansen Jacobus F. A.; Dagnelie Pieter C.; Köhler Sebastian; et al. (Nature Portfolio, 2022)
N-acetylaspartate (NAA) is the second most abundant metabolite in the human brain; although it is assumed to be a proxy for a neuronal marker, its function is not fully elucidated. NAA is also detectable in plasma, but its relation to cerebral NAA levels, cognitive performance, or features of cerebral disease has not been investigated. To study whether circulating NAA tracks cerebral NAA levels, and whether circulating NAA correlates with cognitive function and features of cerebral small vessel disease (SVD). Two datasets were analyzed. In dataset 1, structural MRI was acquired in 533 subjects to assess four features of cerebral SVD. Cognitive function was evaluated with standardized test scores (N = 824). In dataset 2, brain H-1-MRS from the occipital region was acquired (N = 49). In all subjects, fasting circulating NAA was measured with mass spectrometry. Dataset 1: in univariate and adjusted for confounders models, we found no correlation between circulating NAA and the examined features of cerebral SVD. In univariate analysis, circulating NAA levels were associated inversely with the speed in information processing and the executive function score, however these associations were lost after accounting for confounders. In line with the negative findings of dataset 1, in dataset 2 there was no correlation between circulating and central NAA or total NAA levels. This study indicates that circulating NAA levels do not reflect central (occipital) NAA levels, cognitive function, or cerebral small vessel disease in man.